A New Approach to Investment in Algeria - BOUBETRA, Tarek (Journal of Human Sciences, 2025)
The investment law in Algeria has undergone a significant transformation in its relationship with foreign investments. Initially, the system relied on strict oversight of investments to protect the country's economic sovereignty; however, over time, the policy shifted towards a more flexible system to meet global and local economic challenges. This shift has helped attract foreign investments, particularly in new sectors such as manufacturing and renewable energy, contributing to economic diversification and reducing dependence on oil.Recent reforms in investment laws aim to improve the business environment in Algeria by streamlining procedures and providing incentives for investors. Algeria also seeks to enhance its position as a global investment destination while maintaining its economic stability in the face of ongoing challenges. These reforms are a fundamental step towards achieving sustainable economic development and creating job opportunities for citizens.           In this context, the study recommended several steps to improve the investment environment, including simplifying administrative procedures, enhancing education and training to prepare national workforce, supporting innovation and technology, and achieving a balance between protecting economic sovereignty and openness to global investments. It also emphasized the importance of strengthening regional and international cooperation to support the national economy and achieve long-term stability.